Vitamin D measurement standardization: The way out of the chaos. Issue 173 (October 2017) - Binkley, N.; Dawson-Hughes, B.; Durazo-Arvizu, R.; Thamm, M.; Tian, L.; Merkel, J.M.; Jones, J.C.; Carter, G.D.; Sempos, C.T.
Highlights: The lack of standardized laboratory measurement of serum total 25-hydroxyvitamin D [25-OHD] in vitamin D research impedes development of consensus 25-OHD values to define stages of vitamin D status. Some 60, 000 vitamin D papers have been published since the discovery of 25-OHD with nearly all the values from non-standardized assays. We cannot just ignore this old data and focus on standardizing 25-OHD in current and future research. Vitamin D Standardization Program (VDSP) has developed "retrospective standardization" protocols to address this problem. VDSP retrospective standardization of 25-OHD values to gold standard reference measurements values has been shown to be accurate. Retrospective standardization results can vary widely depending on if initial 25-OHD measurements were determined using an assay that was positively or negatively biased and the level of bias in the old assay. An International effort is needed to identify key prior studies with stored samples for re-analysis and standardization, initially, to define the 25-OHD level associated with vitamin D deficiency (rickets/osteomalacia). Subsequent work could focus on defining inadequacy. Finally, levels of assay variation and lack of standardized research data highlight the importance of suspending publication of meta-analyses based on unstandardized 25(OH)D results. Abstract: Substantial variability is associated with laboratory measurement of serum total 25-hydroxyvitamin D [25(OH)D]. The resulting chaos impedes development of consensus 25(OH)D values to define stages of vitamin D status. As resolving this situation requires standardized measurement of 25(OH)D, the Vitamin D Standardization Program (VDSP) developed methodology to standardize 25(OH)D measurement to the gold standard reference measurement procedures of NIST, Ghent University and CDC. Importantly, VDSP developed protocols for standardizing 25(OH)D values from prior research based on availability of stored serum samples. The effect of such retrospective standardization on prevalence of "low" vitamin D status in national studies reported here for The Third National Health and Nutrition Examination Survey (NHANES III, 1988–1994) and the German Health Interview and Examination Survey for Children and Adolescents (KIGGS, 2003–2006) was such that in NHANES III 25(OH)D values were lower than original values while higher in KIGGS. In NHANES III the percentage with values below 30, 50 and 75 nmol/L increased from 4% to 6%, 22% to 31% and 55% to 71%, respectively. Whereas in KIGGS after standardization the percentage below 30, 50, and 70 nmol/L decreased from 28% to 13%, 64% to 47% and 87% to 85% respectively. Moreover, in a hypothetical example, depending on whether the 25(OH)D assay was positively or negatively biased by 12%, the 25(OH)D concentration which maximally suppressed PTH could vary from 20 to 35 ng/mL. These examples underscore the challenges (perhaps impossibility) of developing vitamin D guidelines using unstandardized 25(OH)D data. Retrospective 25(OH)D standardization can be applied to old studies where stored serum samples exist. As a way forward, we suggest an international effort to identify key prior studies with stored samples for re-analysis and standardization initially to define the 25(OH)D level associated with vitamin D deficiency (rickets/osteomalacia). Subsequent work could focus on defining inadequacy. Finally, examples reported here highlight the importance of suspending publication of meta-analyses based on unstandardized 25(OH)D results.